Effects of hypoxia on the mRNA expressions of TRAIL-mediated cell death related genes in hypoxia-tolerant rodent (Nannospalax nehringi) and some characteristics of these proteins - Yıldız, Barış; Kamiloğlu, Nadide Nabil; Öziç , Cem; Coşkun , Yüksel (Archives of Biological Sciences, 2021)
Paper description: TRAIL is a promising anti-cancer agent. Hypoxia is believed to effect TRAIL-mediated cell death (TMCD). Blind mole rats (BMRs) are hypoxia-tolerant rodents and have unique evolutionary characteristics against cancer and hypoxia. Effects of hypoxia on mRNA expressions of TMCD-related genes were detected; six protein sequences in Nannospalax nehringi genes were examined. These genes were regulated differently in the brain compared to the lungs. In addition, many mutations and insertions were found on the conserved regions of the genes. BMRs can contribute to the investigation of the effects of hypoxia on TMCD. Abstract: The aim of the present study was to determine the mRNA expression profiles of TRAIL-mediated cell death related genes of the hypoxia-tolerant rodent Nannospalax nehringi under hypoxia. The nucleotide and amino acid sequences of these genes were identified. Captured Nannospalax nehringi were randomly divided into normoxia and hypoxia groups. The hypoxia group was exposed to a 7% O2 + 93% N2 gas mixture for 52 h, while animals in the normoxia group were housed under normoxic conditions. Total RNAs were isolated from brain and lung tissues. The cIAP-1, cIAP-2, XIAP, DcR1, DcR2, FLIP and OPG genes were PCR amplified, and the cIAP-1, cIAP-2, XIAP, OPG, TRAIL and FLIP genes were sequenced. Sequenced genes were translated into amino acid sequences and compared with reliable sequences of closely similar species. The genes in the brain were regulated for protection against hypoxia; however, the genes in the lung were regulated differently. Many mutations and insertions were observed on the conserved regions of the cIAP-1, cIAP-2, XIAP, OPG and TRAIL genes in N. nehringi. We propose that these gene mutations and insertions contribute to the anti-hypoxic properties of N. nehringi.